2009
DOI: 10.1002/pmic.200900062
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the cold stress response in the moss, Physcomitrella patens

Abstract: Cold stress has adverse effects on plant growth and development. Plants respond and acclimate to cold stress through various biochemical and physiological processes, thereby acquiring stress tolerance. To better understand the basis for tolerance, we carried out a proteomic study in the model moss, Physcomitrella patens, characterizing gametophore proteins with 2-DE and mass spectroscopy. Following exposure to 0 degrees C for up to 3 days, out of the more than 1000 protein spots reproducibly resolved, only 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…Under stress, homoiochlorophyllous plants protect photosystem proteins from degradation due to destruction of chloroplasts (Georgieva et al, 2007). A number of proteomic studies on the moss reaction to drought, high salinity, and low temperature were conducted with use of 2D-electrophoresis (Wang et al, 2008, 2009). It was shown that under drought or salinity, the abundance of light-harvesting proteins increased and the ATP-synthase subunits were down-regulated, but in general there was no significant damage to the photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under stress, homoiochlorophyllous plants protect photosystem proteins from degradation due to destruction of chloroplasts (Georgieva et al, 2007). A number of proteomic studies on the moss reaction to drought, high salinity, and low temperature were conducted with use of 2D-electrophoresis (Wang et al, 2008, 2009). It was shown that under drought or salinity, the abundance of light-harvesting proteins increased and the ATP-synthase subunits were down-regulated, but in general there was no significant damage to the photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that under drought or salinity, the abundance of light-harvesting proteins increased and the ATP-synthase subunits were down-regulated, but in general there was no significant damage to the photosynthetic apparatus. At low temperature, the photosystem and light-harvesting proteins were down-regulated and the dark-phase proteins changed bi-directionally (Wang et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cDNA microarray experiments in Arabidopsis, Narusaka et al (2004) showed abiotic and biotic stress response crosstalk in the expression of cytochrome P450 gene superfamily. In a moss, Physcomitrella patens, cold stress led to up-regulation of cytochrome P450 protein (Wang et al 2009b). Choline-phosphate cytidylyltransferase, also identified in our study, is generally accepted as the rate limiting step in nucleotide pathway of phosphatidyl choline formation, the major component of biological membranes (Vance and Choy 1979).…”
Section: -Chloroacrylic Acid Degradation -?mentioning
confidence: 74%
“…), development stages (seed or tube germination [115,116,[125][126][127]136], fiber elongation [107], fruit senescence [109,137], etc.) and responses to environmental milieu (temperature change [119,[128][129][130], nutritional deficiency or imbalance [102,113], wound [132,133], etc.). To investigate the responses of rice seedlings to H 2 O 2 stress, changes in protein expression were analyzed using a comparative proteomics approach.…”
Section: Plant Proteomicsmentioning
confidence: 99%